Manajemen RKAS di SMA Negeri 13 Surabaya: Kajian Perencanaan, Pengorganisasian, Pelaksanaan, dan Evaluasi - Shalwa P. S., Artamevia; Eldha F., Almas Firdausyah; Sekarsari, Irma Mei; Clarissa, Salsabilla Dwi; Widiyanah, Ima (ARZUSIN, 2026)
School financial management plays an important role in supporting the achievement of educational goals and improving the quality of learning. Although studies on school financial management have been widely conducted, research that specifically discusses the implementation of School Activity and Budget Plan (RKAS) management based on the POAC management functions in public senior high schools remains limited. This study aims to analyze RKAS management at SMA Negeri 13 Surabaya in terms of planning, organizing, implementation, and evaluation aspects. This study used a qualitative approach with a descriptive case study design. The research informants consisted of the principal, the vice principal for public relations, and the school treasurer, who were selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The results show that RKAS management at SMA Negeri 13 Surabaya has systematically applied the POAC management functions. Planning is carried out participatively by involving various parties in the school, organizing is implemented through clear task division and coordination across fields, RKAS implementation is supported by the use of the ARKAS digital system and directed toward improving the quality of learning, while supervision and evaluation are conducted through internal and external monitoring mechanisms. However, RKAS management still faces obstacles in the form of differences in determining program priorities, limited human resources, and administrative burdens in financial reporting. The conclusion of the study affirms that the application of the POAC management functions plays an important role in strengthening systematic, accountable, and learning-quality-oriented RKAS governance. The implications of this study provide theoretical contributions to the development of educational financial management studies, as well as practical implications for schools in strengthening coordination, transparency, and participatory evaluation to improve the effectiveness of RKAS management.